Epidemiology of Dizzy Patient Population in a Neurotology Clinic and Predictors of Peripheral Etiology. Issue 6 (July 2017) - Muelleman, Thomas; Shew, Matthew; Subbarayan, Rahul; Shum, Axel; Sykes, Kevin; Staecker, Hinrich; Lin, James
Abstract : Objective: To compare the proportion of peripheral versus nonperipheral dizziness etiologies among all patients, inclusive of those presenting primarily or as referrals, to rank diagnoses in order of frequency, to determine whether or not age and sex predict diagnosis, and to determine which subgroups tended to undergo formal vestibular testing. Study Design: Retrospective cohort. Setting: Academic neurotology clinic. Patients: Age greater than 18 neurotology clinic patients with the chief complaint of dizziness. Intervention(s): None. Main Outcome Measure(s): Age, sex, diagnosis, record of vestibular testing. Results: Two thousand seventy-nine patients were assigned 2, 468 diagnoses, of which 57.7 and 42.3% were of peripheral and nonperipheral etiologies, respectively. The most common diagnoses were Ménière's (23.0%), vestibular migraine (19.3%), benign paroxysmal positional vertigo (BPPV) (19.1%), and central origin, nonmigraine (16.4%). Peripheral diagnoses are more likely to be found in men than in women (odds ratio [OR] 1.59). Peripheral diagnoses were most likely to be found in the 60 to 69 age group (OR 3.82). There was not a significant difference in rate of vestibular testing between women and men. Among patients with two diagnoses, the most common combinations were vestibular migraine and BPPV then vestibular migraine and Ménière's. Conclusions: A large proportion of patients seen for the chief complaint of dizziness in the neurotology clinic were found not to have a peripheral etiology of their symptoms. These data challenge a prevalent dogma that the most common causes of dizziness are peripheral: BPPV, vestibular neuritis, and Ménière's disease. Age and sex are statistically significant predictors of peripheral etiology of dizziness.